Mismatch repair-based stratification for immune checkpoint blockade therapy - Zhang, Lihong (Am J Cancer Res, 2018)
Mismatch repair (MMR) plays a key role in maintaining genomic stability. Mismatch repair deficiency (MMR-D) causes a molecular feature of microsatellite instability (MSI) and contributes to the development of human cancers and genetic diseases with cancer predisposition such as Lynch syndrome. Recent studies have shown that immune checkpoint blockade therapy has a promising response in MMR-D cancers regardless of the tissue of origin. Being able to identify patients with MMR-D cancers is an important challenge in clinical practice. Although immunohistochemistry (IHC) and polymerase chain reaction (PCR)-based MSI analysis combined with a subsequent MMR gene test are used as the standard of care in the clinical setting to identify patients with MMR-D cancers, these methods have limitations as a pan-cancer testing strategy. Next-generation sequencing (NGS) has developed and matured as a clinical option and NGS has advantages for use as a novel testing strategy for MMR-D detection. In this review, we describe the genetic basis of MMR-D, current diagnostic algorithms in the clinical management of MMR-D, the novel NGS approach, and potential detection strategy of anti-cancer immunity biomarkers of MMR-D.